Preparation method of PbI2 single nanosheet, PbI2 single nanosheet and spin laser

By using a multi-layer transition metal chalcogenide substrate and a fast-temperature-raising tube furnace method in traditional spin lasers, the problems of large size, complex process and low spin rate of traditional spin lasers are solved, and efficient spin laser performance and industrial applicability are achieved.

CN119890907AActive Publication Date: 2025-04-25NAT UNIV OF DEFENSE TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311225070.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-25
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

Traditional spin lasers have large size, complex processes and non-degenerate multi-spin energy levels in the gain material, resulting in a decrease in spin rate. The PbI2 nanosheets with layered structures are extremely sensitive during growth, and are prone to structural defects, affecting their laser performance.

Method used

Using a film layer of multi-layer transition metal chalcogenide as the substrate, a high flatness PbI2 single nanosheet was grown through a rapidly heating tube furnace preparation method, which was used to construct the microcavity structure of a spin laser.

Benefits of technology

The preparation of PbI2 single nanosheets with smooth surface is realized, the laser threshold is lowered, the spin polarization rate is improved, and the process is simple, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890907A_ABST
    Figure CN119890907A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PbI2 single nanosheet, the PbI2 single nanosheet and a spin laser, and the preparation method comprises the following steps: S1, depositing and growing a multilayer transition metal chalcogenide film layer on a substrate as a substrate, and rapidly transferring the substrate to a downstream region of a tube furnace; s2, placing PbI2 powder in a central area of a tubular furnace; and S3, the central area of the tubular furnace is rapidly heated to 380-420 DEG C, heat preservation is conducted for a period of time, meanwhile, the downstream area of the tubular furnace is heated to 210-240 DEG C, and the PbI2 single nanosheet is obtained after cooling. The high-flatness PbI2 single nanosheet can be prepared on the basis that the multi-layer transition metal chalcogenide atomic-level flat surface serves as the substrate for epitaxial growth of the PbI2 material. On the basis that the surface of the PbI2 single nanosheet with the flat atomic level is used as a microcavity, a micro-size spin laser with a low threshold value is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of single nanosheet spin lasers, and in particular to a method for preparing a PbI2 single nanosheet, a PbI2 single nanosheet and a spin laser. Background Art

[0002] Spin lasers have attracted great interest due to their huge application potential in quantum communication, optical information processing and other fields. Traditional spin lasers need to integrate photonic microcavity structures to achieve spin optical gain and obtain spin lasing. This makes traditional spin lasers have a large size (usually mm level) and require a series of complex process preparation processes. In addition, traditional spin gain materials have non-degenerate multi-spin energy levels, which makes spin excitation non-unique, resulting in a decrease in spin rate.

[0003] Recently, lead iodide (PbI2) nanosheets have been reported to show good laser performance and good spin properties, making them ideal candidates for microcavity-free spin lasers. However, the layered structure of PbI2 is extremely sensitive to the growth environment, which affects its direct growth process. PbI2 nanosheets prepared by ordinary preparation methods show many structural defects (such as adsorption structures and lattice defects), which makes their surface roughness fluctuate >4.96nm. Such huge fluctuations prove that ordinary PbI2 nanosheets do not have an excellent optical microcavity themselves, which seriously limits their performance in lasing. Summary of the invention

[0004] The invention provides a method for preparing a PbI2 single nanosheet, a PbI2 single nanosheet and a spin laser, and realizes the preparation of a PbI2 single nanosheet with a smooth surface by adopting a simple process.

[0005] To achieve the above object, the present invention provides a method for preparing a PbI2 single nanosheet, comprising the following steps:

[0006] S1. Depositing and growing a multi-layer film of transition metal chalcogenide on a substrate as a substrate, and quickly transferring the substrate to a downstream area of ​​a tube furnace; wherein multi-layer refers to 6-10 layers;

[0007] S2, placing PbI2 powder in the center area of ​​the tube furnace;

[0008] S3. Rapidly heat the center area of ​​the tube furnace to 380-420°C and keep it warm for a period of time. At the same time, heat the downstream area of ​​the tube furnace to 230-250°C, and obtain PbI2 single nanosheets after cooling; wherein, rapid heating refers to a heating rate of 38-40°C / min.

[0009] To achieve the above object, the present invention also proposes a PbI2 single nanosheet, which is prepared by the above-mentioned preparation method.

[0010] To achieve the above object, the present invention also proposes a spin laser, which uses the above PbI2 single nanosheet as a microcavity structure.

[0011] The advantages of the present invention compared with the prior art are:

[0012] 1. The present invention uses a multi-layer transition metal chalcogenide film as a direct substrate for depositing PbI2, and uses the atomically flat surface of the multi-layer transition metal chalcogenide as a substrate to epitaxially grow PbI2 material, which preliminarily ensures that the epitaxially grown PbI2 also has atomic-level flatness.

[0013] 2. In the process of preparing PbI2 single nanosheets, the present invention rapidly heats the central area of ​​the tube furnace where the PbI2 powder is placed, and combines it with an atomically flat substrate to ultimately prepare a highly flat PbI2 single nanosheet.

[0014] 3. The preparation method of the present invention has a wide range of raw materials, a simple production process, and is suitable for industrialization.

[0015] 4. The thickness of the PbI2 single nanosheet prepared by this method is 450-600nm. Since PbI2 is a semiconductor, its band gap corresponds to a light emission wavelength of about 510nm. Therefore, a smaller thickness cannot confine the light of this wavelength, and thus the resonance of lasing cannot occur. A larger thickness is close to an integer multiple of 1 or 2 times half the light emission wavelength, which can well confine the light emission to form resonance and reduce the laser threshold.

[0016] 5. The PbI2 single nanosheet prepared by this method has a smooth surface, thus forming an excellent microcavity structure, and the threshold can be lower than 10μJ / cm at a low temperature of 20K. 2 The ultra-low threshold laser of a single nanosheet is one order of magnitude lower than that of ordinary lead iodide PbI2 single nanosheet (reported to be 250μJ / cm 2 and 126.2 μJ / cm 2 ). Near the threshold, due to the low exciton density, the exciton spin relaxation effect is greatly reduced, thus achieving a spin polarization rate of up to 68% at the lasing wavelength. This polarization is much larger than the fluorescence spin polarization of ordinary PbI2 single nanosheets (about 10%), and much larger than the spin lasing polarization of ordinary lead iodide PbI2 single nanosheets (about 0%), such as Fig. 9 shown.

[0017] 6. The spin laser of the present invention realizes spin laser only by relying on its own microcavity of nanosheet size, which is the first micro spin laser realized. The spin laser reported in the past needs to be combined with an optical microcavity so that the typical size is in the millimeter level, and the preparation process is complicated. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0019] Figure 1 The test results of multilayer WS2; a is an optical image, b is an atomic force microscope image of the surface, and c is an atomic force microscope line scan. The scale is 5 μm. It can be seen that the thickness of the multilayer WS2 is 4.2 nm and the roughness is less than 0.3 nm.

[0020] Figure 2 This is a test image of the optimized PbI2 single nanosheet obtained in Example 1; where: i is an optical image with a thickness of about 511nm, ii is a surface atomic force microscope image (range 2μm×2μm), and iii is an atomic force microscope line scan image with a roughness of <0.5nm. The scale bar is 5μm;

[0021] Figure 3 At 300K, σ - Photoexcited σ + and σ - Fluorescence polarization spectroscopy;

[0022] Figure 4 is the spin polarization rate at 20K-300K;

[0023] Figure 5 is the σ of fluorescence emission in the wavelength range of 488-508 nm - and σ + Light attenuation curve over time;

[0024] Figure 6 The excitation energy is 16.3 μJ / cm 2 , the temperature is 20K, the wavelength range is 488-508nm, the optimized lead iodide PbI2 single nanosheet polarization spectrum and spin polarization rate value;

[0025] Figure 7 The fluorescence spectra of the optimized PbI2 single nanosheet just prepared and the optimized lead iodide PbI2 single nanosheet after deposition for 1 month, and the corresponding normalized fluorescence intensity diagram;

[0026] Figure 8 The test results of ordinary PbI2 nanosheets, where a is an optical image, b is an atomic force microscope image of the surface (range is 2μm×2μm), and c is an atomic force microscope line scan image; the scale bar is 5μm;

[0027] Fig. 9 is the spin lasing polarization of ordinary PbI2 single nanosheet;

[0028] Fig.10 The results of Raman spectroscopy research; wherein: (a) is the Raman spectra collected from ordinary and optimized lead iodide PbI2 single nanosheets, (b) is the normalized Raman spectra of ordinary and optimized lead iodide PbI2 single nanosheets;

[0029] Fig.11 This is the fluorescence spectrum research result;

[0030] Fig.12 It is a function diagram of fluorescence intensity and the inverse of temperature 1 / T; wherein: (a) is a function diagram of fluorescence intensity of ordinary lead iodide PbI2 single nanosheet as 1 / T, (b) is a function diagram of fluorescence intensity of optimized lead iodide PbI2 single nanosheet as 1 / T;

[0031] Fig.13 is the graph of fluorescence intensity and excitation power function;

[0032] Fig.14 To optimize the laser threshold performance results of lead iodide PbI2 single nanosheets;

[0033] Fig.15 This is the laser threshold performance result of ordinary lead iodide PbI2 single nanosheet. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0036] The present invention provides a method for preparing a PbI2 single nanosheet, comprising the following steps:

[0037] S1. Depositing and growing a multi-layer film of transition metal chalcogenide on a substrate as a substrate, and quickly transferring the substrate to a downstream area of ​​a tube furnace; wherein multi-layer refers to 6-10 layers;

[0038] S2, placing PbI2 powder in the center area of ​​the tube furnace;

[0039] S3. Rapidly heat the center area of ​​the tube furnace to 380-420° C. and keep it warm for a period of time. Meanwhile, heat the downstream area of ​​the tube furnace to 230-250° C., and obtain PbI2 single nanosheets after cooling.

[0040] Herein, a single nanosheet refers to a single-layer nanosheet.

[0041] Rapid heating refers to a heating rate of 38-40°C / min. The purpose of rapid heating is to ensure that the source evaporates as quickly as possible to form an atmosphere.

[0042] The central area of ​​the tubular furnace for preparing PbI2 single nanosheets is the high-temperature evaporation zone, and the downstream area is the low-temperature deposition zone.

[0043] Preferably, in step S1, the specific step of depositing and growing a multi-layer transition metal sulfide compound film layer is: preparing the deposited and grown multi-layer transition metal sulfide compound film layer by adopting a physical vapor deposition method.

[0044] Preferably, in step S1, in step S1, the transition metal chalcogenide is one or more of tungsten disulfide, tungsten diselenide, molybdenum disulfide, molybdenum diselenide or molybdenum ditelluride. Among them, the PbI2 single nanosheet prepared using disulfide as the substrate is the flattest.

[0045] If the transition metal sulfide is tungsten disulfide, when a multilayer film of the transition metal sulfide is deposited and grown in a tube furnace by physical vapor deposition, the growth temperature is 1120-1170°C and the deposition temperature is 750-770°C.

[0046] If the transition metal chalcogenide is tungsten diselenide, when a multilayer film of the transition metal chalcogenide is deposited and grown in a tube furnace by physical vapor deposition, the growth temperature is 1070-1100°C and the deposition temperature is 750-770°C.

[0047] In this scheme, two tube furnaces are required. The first tube furnace is used to prepare multilayer transition metal chalcogenides, and the second tube furnace is used to epitaxially grow PbI2 on multilayer transition metal chalcogenides. The two materials require different growth temperatures, and the two tube furnaces can ensure that the growth sources between the two materials do not contaminate each other to avoid defects in the materials.

[0048] Preferably, the base in step S1 is a silicon substrate having a silicon oxide film.

[0049] Preferably, step S2 further includes:

[0050] The pressure of the tube furnace system was reduced to less than 20 mtorr by a vacuum pump while maintaining an argon flow rate of 38-40 sccm. Using argon as a carrier gas helps to obtain a flat surface.

[0051] The present invention also provides a PbI2 single nanosheet, which is prepared by the above preparation method. The thickness of the PbI2 single nanosheet is 450-600nm and the roughness is less than 0.5nm.

[0052] The present invention also provides a spin laser, which uses the above-mentioned PbI2 single nanosheet as a microcavity structure.

[0053] Embodiment 1:

[0054] High-quality lead iodide PbI2 single nanosheets were prepared on a 7-layer tungsten disulfide WS2 substrate.

[0055] Step 1: Preparation of 7 layers of tungsten disulfide WS2 film.

[0056] 1. Seven layers of tungsten disulfide WS2 film are grown on a silicon substrate with a silicon oxide film by physical vapor deposition.

[0057] The specific preparation control conditions are: the center temperature of the tube furnace is 1170° C., the downstream deposition temperature is 770° C., and the argon atmosphere has a gas flow rate of 40 sccm.

[0058] Among them, the multilayer characteristics of transition metal chalcogenides make them flat at the atomic scale. Figure 1 As shown, the test results of multilayer WS2 are provided, where: a is an optical image, b is an atomic force microscope imaging of the surface, and c is an atomic force microscope line scan image. The scale is 5μm. It can be seen that the thickness of the multilayer WS2 is 4.2nm (corresponding to 7 layers) and the roughness is less than 0.3nm.

[0059] Step 2: Preparation of lead iodide PbI2 single nanosheets.

[0060] 1. Quickly transfer the substrate with 7 layers of tungsten disulfide WS2 film to the downstream area of ​​another tube furnace.

[0061] 2. Place the PbI2 powder in the center of the tube furnace and use the carrier gas to guide the steam source to prepare high-quality lead iodide PbI2 single nanosheets.

[0062] The specific preparation control conditions are: reduce the system pressure to less than 20mtorr through a vacuum pump; maintain an argon flow rate of 40sccm at the same time; rapidly increase the temperature to 400°C and maintain it at this temperature for 20 minutes; after optimizing the deposition temperature to 235°C, a single lead iodide (PbI2) nanosheet with a thickness of 511nm can be successfully obtained.

[0063] The test picture of the optimized lead iodide PbI2 single nanosheet is as follows Figure 2 As shown, i is an optical image with a thickness of about 511 nm, ii is an atomic force microscope image of the surface (range 2 μm×2 μm), and iii is an atomic force microscope line scan image with a roughness of <0.5 nm. The scale bar is 5 μm.

[0064] Take the optimized lead iodide PbI2 single nanosheet in Example 1 as an example to perform corresponding performance tests

[0065] Test 1: Spin property test (circular polarization experiment)

[0066] Test steps:

[0067] Step 1: σ+ and σ- Defined as the detected σ + and σ - Polarized emission intensity. + and σ - Under polarized excitation light, the spin polarization rate can be defined as ρ = (I σ- / σ+ -Ι σ+ / σ- ) / (Ι σ+ +Ι σ- ).

[0068] Step 2: Draw the optimized lead iodide PbI2 single nanosheet at 300K by σ - Photoexcited σ + and σ - Polarization spectrum.

[0069] Step 3: Study the change of spin polarization as the temperature decreases.

[0070] Test results:

[0071] 1. σ - The main emission (black) has a spin polarization of ~22.1%, as Figure 3 shown.

[0072] 2. A spin polarization of 36.3% is obtained at 20K, such as Figure 4 shown.

[0073] Test 2: Spin-flip life test

[0074] Test steps:

[0075] Step 1: Figure 5 As shown, the σ of the fluorescence emission in the wavelength range of 488-508 nm was measured using a streak camera. - (black) and σ + (Red) Decay curve. The gray dashed line represents the instrument response function (IRF) obtained from the excitation light.

[0076] Step 2: Based on these two spin polarization curves, plot the spin polarization rate as a function of decay time.

[0077] Step 3: Fit the curve using a single exponential decay equation: I(t) = exp(-t / τ F ). Where I(t) is the emission intensity at decay time t, and τ F is the time constant of the spin flip.

[0078] Test results: Fitting the above curve shows that τ F The long time constant is 48.2ps.

[0079] Conclusion: τ F The long time constant of 48.2ps is much longer than the 15ps previously reported in ordinary lead iodide PbI2 single nanosheets. This means that the spin flip process is greatly suppressed, and the spin flip rate (1 / τ) of the optimized lead iodide PbI2 single nanosheet is F ) is lower than that of ordinary lead iodide PbI2 single nanosheets.

[0080] Test 3: Test of spin laser polarizability

[0081] Test environment: spontaneous radiation wavelength: 498.9nm, excitation light energy: 16.3μJ / cm 2 , temperature: 20K

[0082] Test results: Figure 6 As shown, when the laser wavelength is 498.9nm, the temperature is 20K, and the excitation light energy is 16.3μJ / cm 2 Under these conditions, a spin polarization rate as high as 62.8% can be obtained.

[0083] Taking the optimized lead iodide PbI2 single nanosheet in Example 1 as an example, the optical stability of the optimized lead iodide PbI2 single nanosheet during preparation was compared with that of the optimized lead iodide PbI2 single nanosheet after deposition for one month.

[0084] The fluorescence spectra of the optimized lead iodide PbI2 single nanosheet during preparation and the optimized lead iodide PbI2 single nanosheet one month after deposition are plotted respectively, as well as the corresponding normalized spectrum graph and normalized fluorescence intensity graph.

[0085] like Figure 7 As shown, (a) is the fluorescence spectrum during preparation and one month after deposition; the inset in (a) is the corresponding normalized spectrum. (b) is the normalized fluorescence intensity under light excitation.

[0086] It can be observed that the two fluorescence spectra show almost unchanged peak shape and similar intensity, indicating that the optimized PbI2 single nanosheet has good atmospheric stability. Over time, the optimized lead iodide PbI2 single nanosheet exhibits an almost constant fluorescence intensity, indicating that it has good photoexcitation stability.

[0087] Comparative test conclusion: The stability study of optimized lead iodide PbI2 single nanosheets proves the higher quality of optimized PbI2, and the deposition and photoexcitation stability of optimized lead iodide PbI2 single nanosheets are improved. The improvement of the quality of lead iodide PbI2 single nanosheets will bring significant physical and photonic features.

[0088] Comparative Example 1

[0089] PbI2 was directly deposited on a silicon substrate with a silicon oxide film using a tube furnace. PbI2 was placed as a source in the center of the tube furnace, the center temperature was 400°C, and the deposition temperature was 280°C. The center was quickly heated to 400°C and maintained for 20 minutes before naturally cooling to room temperature to obtain a common PbI2 single nanosheet.

[0090] The test results of ordinary PbI2 single nanosheets are as follows Figure 8 As shown, where: (a) is an optical image with a thickness of approximately 524 nm, (b) is an atomic force microscope image of the surface (range is 2 μm × 2 μm), and (c) is an atomic force microscope line scan image with a roughness of >4.9 nm and a scale bar of 5 μm.

[0091] The spin lasing polarization of ordinary lead iodide PbI2 single nanosheet (about 0%), such as Fig. 9 shown.

[0092] In order to verify the performance of the optimized lead iodide PbI2 single nanosheet, the present invention conducted the following test experiments on the optimized lead iodide PbI2 single nanosheet in Example 1 and the ordinary lead iodide PbI2 single nanosheet, and the comparison results are as follows:

[0093] Comparative test 1: Raman spectroscopy research test

[0094] Plotting the Raman spectra of ordinary and optimized lead iodide PbI2 single nanosheets.

[0095] Fig.10 (a) Raman spectra collected from ordinary and optimized PbI2 single nanosheets. (b) Normalized Raman spectra of ordinary and optimized PbI2 single nanosheets.

[0096] Detection of E in common lead iodide PbI2 single nanosheets g (74.7cm -1 ), A 1g (97.5cm -1 ) and A 2u (113.8cm -1 ) three typical vibration modes. The optimized lead iodide PbI2 single nanosheet was detected. In addition to the three modes of PbI2, two vibration modes of 7-layer tungsten disulfide WS2 (351.0 cm -1 E 2g and 421.8cm -1 A 1g ).

[0097] In addition, it can be observed that the pattern of the optimized PbI2 single nanosheet shows an obvious blue shift compared with the ordinary PbI2 single nanosheet. g The peak position is 71.8 cm -1 , A 1g The peak position is 95.5 cm -1 and A 2u The peak position is 110.8 cm -1 .

[0098] Comparative test 2: PL spectrum test

[0099] Draw a fluorescence spectrum, such as Fig.11 shown.

[0100] Compared with ordinary lead iodide PbI2 single nanosheets, the fluorescence intensity of the optimized lead iodide PbI2 single nanosheets is greatly enhanced, with a multiplication factor of about 6.4 times.

[0101] The full width at half maximum (FWHM) of the optimized lead iodide PbI2 single nanosheet is greatly reduced from 25.1nm (ordinary lead iodide PbI2 single nanosheet) to 12.7nm. The fluorescence peak of the optimized PbI2 is blue-shifted from 515.1nm (ordinary PbI2) to 504.8nm.

[0102] Comparative test three: temperature related experiments

[0103] like Fig.12 The temperature-dependent experiment is shown.

[0104] (a) The fluorescence intensity of ordinary lead iodide (PbI2) single nanosheets and (b) optimized lead iodide (PbI2) single nanosheets as a function of 1 / T, where T is the measurement temperature.

[0105] According to the equation: Where E b is the exciton binding energy, K B is the Boltzmann constant and we fit the data via the Arrhenius relation.

[0106] The binding energy of ordinary PbI2 was fitted to ~27.4 meV, close to the activation energy at room temperature.

[0107] The exciton binding energy of the optimized PbI2 is ~42.8 meV, which is significantly higher than the activation energy at room temperature.

[0108] Comparative test 4: power-related experiments

[0109] like Fig.13 Shown: Power-related experiment.

[0110] Double logarithmic curve function graph of fluorescence intensity and excitation power of ordinary lead iodide PbI2 single nanosheets and optimized lead iodide PbI2 single nanosheets.

[0111] The superlinear / quasi-linear power-law index of ordinary lead iodide PbI2 single nanosheets / optimized lead iodide PbI2 single nanosheets is ~1.588 / ~1.173, indicating that its quasiparticle types are free carriers / excitons.

[0112] Comparative Test 5: Laser properties of lead iodide PbI2 single nanosheet at low temperature of 20K

[0113] The threshold power of the laser process is tested by linearly polarized pulse laser excitation.

[0114] After testing, at a low temperature of 20K, the threshold power of the optimized lead iodide PbI2 single nanosheet in the laser process is 15.1μJ / cm 2 , where the half-width decreases from ∼2.5 to ∼1.2 nm, and the emission intensity increases rapidly, e.g. Fig.14 shown.

[0115] In the common lead iodide PbI2 single nanosheet, 112.4 μJ / cm 2 The high threshold of the laser peak is about 2.4nm. Fig.15 shown.

[0116] Comparative test conclusion:

[0117] 1. Raman spectroscopy experiments observed that the blue-shifted Raman mode of the optimized lead iodide PbI2 single nanosheets indicated that its lattice quality may be better than that of ordinary lead iodide PbI2 single nanosheets, because defect doping always leads to a red shift in the Raman spectrum. It was further detected that the background scattering of the Raman spectrum in the optimized PbI2 was lighter than that in ordinary PbI2, indicating that the optimized lead iodide PbI2 single nanosheets had higher lattice quality than ordinary lead iodide PbI2 single nanosheets.

[0118] 2. Based on the fluorescence intensity spectrum, the radiative recombination of the optimized lead iodide (PbI2) single nanosheet is enhanced compared with that of the ordinary lead iodide (PbI2) single nanosheet.

[0119] 3. Temperature-dependent spectroscopy experiment ( Fig.11 ) showed that the exciton features were enhanced in lead iodide (PbI2) single nanosheets due to the increase in the exciton binding energy from 27.4 meV (normal PbI2) to 42.8 meV (optimized PbI2).

[0120] 4. Power correlation spectroscopy experiment ( Fig.12 ) showed that at room temperature, the dominant quasiparticle species transfers from free carriers in ordinary lead iodide (PbI2) single nanosheets to excitons in optimized lead iodide (PbI2) single nanosheets.

[0121] 5. The optimized lead iodide PbI2 single nanosheet achieved a low threshold of 15.1μJ / cm 2 High performance laser.

[0122] Test equipment and parameters:

[0123] Optical characterization. Raman spectroscopy was performed with a confocal microscope (WITec, alpha-300) using a 532 nm continuous wave laser as the light source (incident power 200 μW). Steady-state fluorescence luminescence spectroscopy experiments were performed with the same system, but using a 400 nm continuous wave laser as the excitation light (excitation power 4 μW). Fluorescence luminescence intensity experiments dependent on the excitation power were performed at different excitation powers. Temperature-dependent fluorescence luminescence experiments were performed using an additional microscope cryostat system (C01-001-122, LINKPHYSICS).

[0124] Laser experiments. Laser experiments were performed using a confocal microscope (WITec, alpha-300). A mode-locked Ti:Sapphire laser (Tsunami) at 800 nm (pulse width 80 fs, repetition rate 80 MHz) was amplified by a regenerative amplifier laser (Spitfire Ace100, 1 KHz) and then introduced into an optical parametric amplifier (OPA, TOPAS Prime). The 470 nm wavelength output laser of the OPA was used as the light source for the laser experiments.

[0125] TRPL experiments. TRPL experiments were performed with a streak camera (C10910, Hamamatsu) using the same excitation light as in the laser experiments. The decay curves were centered in the wavelength range of 488–508 nm. The excitation light was a 400 nm pulsed laser, derived from the mode-locked Ti:sapphire laser described above, passed through a barium metaborate crystal to generate the second harmonic.

[0126] Circular polarization experiments. A linear polarizer and a quarter wave plate are used in the incident beam to produce high quality circularly polarized light. The PL signal is checked by the quarter wave plate and the polarizer by rotating the polarizer. The main system is the same as above. All circular polarization experiments are performed by σ - Optically pumped.

[0127] Embodiment 2:

[0128] High-quality lead iodide PbI2 single nanosheets were prepared on a 7-layer tungsten disulfide WS2 substrate.

[0129] Step 1: Preparation of 7 layers of tungsten disulfide WS2 film.

[0130] 1. Grow 7 layers of tungsten disulfide WS2 film by physical vapor deposition.

[0131] The specific preparation control conditions are: the center temperature of the tube furnace is 1170° C., the downstream deposition temperature is 750° C., and the argon atmosphere has a gas flow rate of 40 sccm.

[0132] Step 2: Preparation of lead iodide PbI2 single nanosheets.

[0133] 1. Quickly transfer the substrate with 7 layers of tungsten disulfide WS2 film to the downstream area of ​​another tube furnace.

[0134] 2. Place the PbI2 powder in the center of the tube furnace and use the carrier gas to guide the steam source to prepare high-quality lead iodide PbI2 single nanosheets.

[0135] The specific preparation control conditions are: reduce the system pressure to less than 18mtorr through a vacuum pump; maintain an argon flow rate of 60sccm at the same time; rapidly increase the temperature to 390°C and maintain it at this temperature for 20 minutes; after optimizing the deposition temperature to 245°C, we can successfully obtain lead iodide (PbI2) single nanosheets with a thickness of 480nm and a roughness of <0.5nm.

[0136] Taking Example 1 as a benchmark, as shown in Table 1, the roughness of PbI2 single nanosheets corresponding to 1 to 5 layers of WS2 is provided below.

[0137] Table 1 Roughness of PbI2 single nanosheets corresponding to 1 to 5 layers of WS2

[0138] <![CDATA[Number of WS2 layers]]> <![CDATA[Roughness of PbI2 single nanosheet / nm]]> 1 >8.3 2 >6.6 3 >2.7 4 >2.9 5 >1.4

[0139] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. Therefore, the scope of protection of the present invention should be subject to the scope of protection of the claims.

Claims

1. A method for preparing a PbI2 single nanosheet, characterized in that: The following steps are involved: S1. Depositing and growing a multi-layer film of transition metal chalcogenide on a substrate as a substrate, and quickly transferring the substrate to a downstream area of ​​a tube furnace; wherein multi-layer refers to 6-10 layers; S2, placing PbI2 powder in the center area of ​​the tube furnace; S3. Rapidly heat the center area of ​​the tube furnace to 380-420°C and keep it warm for a period of time. At the same time, heat the downstream area of ​​the tube furnace to 230-250°C, and obtain PbI2 single nanosheets after cooling; wherein, rapid heating refers to a heating rate of 38-40°C / min.

2. The preparation method according to claim 1, characterized in that: In step S1 , the specific steps of depositing and growing a multi-layer transition metal chalcogenide film layer are: preparing and depositing a multi-layer transition metal chalcogenide film layer by adopting a physical vapor deposition method.

3. The preparation method according to claim 1, characterized in that: In step S1 , the transition metal chalcogenide is one or more of tungsten disulfide, tungsten diselenide, molybdenum disulfide, molybdenum diselenide or molybdenum ditelluride.

4. The preparation method according to claim 3, characterized in that: If the transition metal sulfide is tungsten disulfide, when a multilayer film of the transition metal sulfide is deposited and grown in a tube furnace by physical vapor deposition, the growth temperature is 1120-1170°C and the deposition temperature is 750-770°C.

5. The preparation method according to claim 3, characterized in that: If the transition metal chalcogenide is tungsten diselenide, when a multilayer film of the transition metal chalcogenide is deposited and grown in a tube furnace by physical vapor deposition, the growth temperature is 1070-1100°C and the deposition temperature is 750-770°C.

6. The preparation method according to claim 1, characterized in that: Step S2 also includes: The tube furnace system pressure was reduced to less than 20 mtorr by a vacuum pump while maintaining an argon flow rate of 38-40 sccm.

7. The preparation method according to claim 1, characterized in that: The base in step S1 is a silicon substrate having a silicon oxide film.

8. A PbI2 single nanosheet, characterized in that: The PbI2 single nanosheet is prepared by the preparation method described in any one of claims 1 to 7; the thickness of the PbI2 single nanosheet is 450 to 600 nm, and the roughness is less than 0.5 nm.

9. A spin laser, characterized in that: A PbI2 single nanosheet prepared by the preparation method according to any one of claims 1 to 7 or a PbI2 single nanosheet according to claim 8 is used as the microcavity structure.

Citation Information

Patent Citations

  • Controlled synthesis method for PbI2 micro-nano structure

    CN106809874A

  • Lead iodide nanometer material, and preparation method and applications thereof

    CN110104675A

  • Method for regulating and controlling growth of lead iodide by single-layer molybdenum sulfide

    CN110230039A

  • Preparation method and application of two-dimensional lead iodide sheet

    CN110611015A

  • Method for preparing ultrathin lead iodide nanosheet and converting ultrathin lead iodide nanosheet into ultrathin perovskite nanosheet

    CN115896915A